Land Cover Change Prediction Modeling in Tanjungpinang City in 2043 - Arie Afriadi; Nefriwati Hilmi; Hoki Apriyenson; Zuleriwati AS (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2025)
Land cover changes reflect the pressure of development and increased human activities that have an impact on environmental imbalance. As a strategic coastal city, Tanjungpinang faces challenges in maintaining the sustainability of its regional ecosystem. This study aims to analyze the dynamics of land cover changes and predict their conditions until 2043 using remote sensing technology and geographic information systems (GIS), incorporating Cellular Automata and logistic regression methods. The results of the study showed that land cover changes between 2003 and 2023 increased built-up area by 27.15 km² and decreased Vegetation by 14.02 km². Bare Land increased by 1.45 km² at the beginning of the period, then reduced to a total of 12.74 km². Water bodies decreased by 0.39 km². Predictions for 2043 indicate that built-up area increased by 5.12 square kilometres, while Vegetation decreased by 6.33 square kilometres. Bare land increased by 1.34 km², while water bodies declined by 0.14 km². This pattern indicates a trend of converting vegetative land into built-up areas due to the increasing demand for regional space.